Terapi Controller pada Asma - Alexander Kam; Fauzar Fauzar; Roza Kurniati; Zulkarnain Arsyad (Jurnal Ilmu Kesehatan Indonesia, 2021)
Asthma, according to the National Heart Lung and Blood Institute (NHBLI) in 2002, is a chronic inflammatory disorder of the airways that involves the role of many cells and cellular components. The long-term goals of asthma management are to achieve good symptom control and maintain normal living activities and to minimize the risk of exacerbations, airway obstruction, and side effects. The drugs available for asthma therapy are divided into long-term control or controller medication and rapid-acting or reliever medication based on their pharmacodynamics and clinical effects. Controller is a therapy given to reduce chronic airway inflammation, control symptoms, and reduce the risk of exacerbations and decreased lung function. There are several asthma controller drug options that have their respective advantages and disadvantages. Selection of the right controller will provide good asthma control. Keyword: Ashtma, therapy, controller